Histone deacetylase functions and therapeutic implications for adult skeletal muscle metabolism - Molinari, Susanna; Imbriano, Carol; Moresi, Viviana; Renzini, Alessandra; Belluti, Silvia; Lozanoska-Ochser, Biliana; Gigli, Giuseppe; Cedola, Alessia (Frontiers in Molecular Biosciences, 2023)
Skeletal muscle is a highly adaptive organ that sustains continuous metabolic changes in response to different functional demands. Healthy skeletal muscle can adjust fuel utilization to the intensity of muscle activity, the availability of nutrients and the intrinsic characteristics of muscle fibers. This property is defined as metabolic flexibility. Importantly, impaired metabolic flexibility has been associated with, and likely contributes to the onset and progression of numerous pathologies, including sarcopenia and type 2 diabetes. Numerous studies involving genetic and pharmacological manipulations of histone deacetylases (HDACs) in vitro and in vivo have elucidated their multiple functions in regulating adult skeletal muscle metabolism and adaptation. Here, we briefly review HDAC classification and skeletal muscle metabolism in physiological conditions and upon metabolic stimuli. We then discuss HDAC functions in regulating skeletal muscle metabolism at baseline and following exercise. Finally, we give an overview of the literature regarding the activity of HDACs in skeletal muscle aging and their potential as therapeutic targets for the treatment of insulin resistance.